COVID-19 Respiratory Failure: Targeting Inflammation on VV-ECMO Support. Issue 6 (June 2020) - Hartman, Matthew E.; Hernandez, Roland A.; Patel, Krish; Wagner, Teresa E.; Trinh, Tony; Lipke, Anne B.; Yim, Eric T.; Pulido, Juan N.; Pagel, John M.; Youssef, Samuel J.; Mignone, John L.
Abstract : The outbreak of novel coronavirus (SARS-CoV-2) that causes the respiratory illness COVID-19 has led to unprecedented efforts at containment due to its rapid community spread, associated mortality, and lack of immunization and treatment. We herein detail a case of a young patient who suffered life-threatening disease and multiorgan failure. His clinical course involved rapid and profound respiratory decompensation such that he required support with venovenous extracorporeal membrane oxygenation (VV-ECMO). He also demonstrated hyperinflammation (C-reactive protein peak 444.6 mg/L) with severe cytokine elevation (Interleukin-6 peak > 3000 pg/ml). Through treatment targeting hyperinflammation, he recovered from critical COVID-19 respiratory failure and required only 160 hours of VV-ECMO support. He was extubated 4 days after decannulation, had progressive renal recovery, and was discharged to home on hospital day 24. Of note, repeat SARS-CoV-2 test was negative 21 days after his first positive test. We present one of the first successful cases of VV-ECMO support to recovery of COVID-19 respiratory failure in North America. Abstract : Supplemental Digital Content is available in the text.